How Language Matters: Using Ethnographic Writing to Portray and Reflect on Languaging Actions. Issue 2 (2nd August 2021) - Beach, Richard; Caraballo, Limarys
Abstract: This study examined 12th‐grade students' portrayals of their use of different types of languaging actions through ethnographic writing about their participation in sports teams or peer groups and explicit prompted reflections about their languaging actions portrayed in their writing. Analysis of different types of languaging actions indicated that students were most likely to portray and reflect on actions related to building supportive relations with others. They also identified actions involving enacting roles/identities, using "insider language, " expression of beliefs/values and emotions/feelings, coping with conflicts, use of humor/joking, assuming leadership roles, and interacting with adults/coaches. These results suggest the value of students using writing to portray and reflect on the use of languaging actions to enact relations with others, reflection that serves to foster growth in their languaging over time. There is also a need for further research on students' use of writing to portray different types of supportive relations through languaging.